2017
DOI: 10.1186/s12939-017-0590-2
|View full text |Cite
|
Sign up to set email alerts
|

Health-care users, key community informants and primary health care workers’ views on health, health promotion, health assets and deficits: qualitative study in seven Spanish regions

Abstract: BackgroundAlthough some articles have analysed the definitions of health and health promotion from the perspective of health-care users and health care professionals, no published studies include the simultaneous participation of health-care users, primary health care professionals and key community informants. Understanding the perception of health and health promotion amongst these different stakeholders is crucial for the design and implementation of successful, equitable and sustainable measures that impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…However, we acknowledge that the current version of this intervention cannot yet be integrated in primary care practice until fundamental organisational changes that ensure feasibility and sustainability in real-world conditions take place. Even though the intervention was adapted and implemented following the recommendations of healthcare attendees and health professionals obtained in prior phases of the EIRA Project,2 3 8–10 further adjustments are required. For instance, in the EIRA Project, we concluded that for health promotion, it is essential to involve most primary care professionals, including administrative staff, to avoid tension and to challenge the notion that health promotion is voluntary or based on personal preference.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we acknowledge that the current version of this intervention cannot yet be integrated in primary care practice until fundamental organisational changes that ensure feasibility and sustainability in real-world conditions take place. Even though the intervention was adapted and implemented following the recommendations of healthcare attendees and health professionals obtained in prior phases of the EIRA Project,2 3 8–10 further adjustments are required. For instance, in the EIRA Project, we concluded that for health promotion, it is essential to involve most primary care professionals, including administrative staff, to avoid tension and to challenge the notion that health promotion is voluntary or based on personal preference.…”
Section: Discussionmentioning
confidence: 99%
“…The EIRA Project started in Spain in 2012 with the objective to modify unhealthy behaviours in primary care patients following the MRC framework for complex interventions 6 7. To date, the first three phases have been completed 2 3 8–10. Specifically, the objective of the EIRA Project was to design, conduct and evaluate a complex, multirisk intervention to enhance adherence to the Mediterranean diet, increase insufficient physical activity and reduce smoking, cardiovascular risk factors and risk of depression in people aged 45–75 years that contact PHC services with at least two of these behaviours or risk factors.…”
Section: Introductionmentioning
confidence: 99%
“…The execution of health services is undertaken by local health and medical institutions, mainly by public health centers (health and medical centers), health care centers, and health promotion centers. In the meantime, the performance management for health services is evaluated by local governments and public health centers [32][33][34]. (Figure 1).…”
Section: Central Health Institutionmentioning
confidence: 99%
“…The intervention was based on the Transtheoretical Model and Stages of Change [29,31] and was built on the results of the previous phases of the EIRA study [11,20,29,[21][22][23][24][25][26][27][28]. It had a maximum duration of 12 months and was carried out at the individual, group and community level in accordance to the stages of change and unhealthy behaviours (see Table 1).…”
Section: Interventionmentioning
confidence: 99%
“…Regarding this, the effectiveness-implementation hybrid trials with their dual approach offer the opportunity to assess the effectiveness of both an intervention and an implementation strategy [17,18] In 2012, the Spanish Primary Care Prevention and Health Promotion Research Network (redIAPP) [19] launched the EIRA study, a MHBC intervention targeting three unhealthy behaviours in people aged 45 to 75. The rst three phases (preclinical phase, phase I and phase II) followed the MRC framework [11,20,29,[21][22][23][24][25][26][27][28]. This article describes the results of phase III, in which we used a hybrid design with the aim of evaluating the effectiveness of a) a 12-month MHBC primary care intervention on reducing smoking, increasing physical activity and enhancing adherence to a Mediterranean dietary pattern in people aged 45-75 years compared to usual care; and b) an implementation strategy in terms of acceptability, adoption, appropriateness, feasibility and delity.…”
Section: Introductionmentioning
confidence: 99%